Contactless and Spatially Resolved Determination of Current−Voltage Curves in Perovskite Solar Cells via Photoluminescence. Issue 8 (6th June 2021) - Bui, Anh Dinh; Mahmud, Md Arafat; Mozaffari, Naeimeh; Basnet, Rabin; Duong, The; Bartholazzi, Gabriel; Le, Tien T.; Truong, Thien N.; Tebyetekerwa, Mike; Wibowo, Ary; Weber, Klaus J.; White, Thomas P.; et al.
Abstract : Early prediction of spatially resolved performance of perovskite solar cells (PSCs) is essential for process monitoring, control and fault diagnosis, and upscaling of this emerging technology. Herein, a fast, nonde structive, contactless imaging‐based approach is developed to visualize the spatial distribution of possible light current density−voltage (pseudo‐ J−V ) curves on finished and partly finished cells. This allows for the extraction of other critical spatially resolved properties including implied open‐circuit voltage and pseudo‐fill factor. The technique is applied to systematically investigate various degradation behaviors on PSCs including thermal stability, light soaking, and ambient air exposure. Finally, it is used to predict pseudo‐ J−V curves of various perovskite films with different compositions. These results demonstrate the significant value of this fast imaging technique for the research and development of PSCs ranging from material selection, process optimization, to degradation study. Abstract : Suns‐photoluminescence approach is used to spatially resolve open‐circuit voltages and pseudo‐fill factors of finished and partially finished perovskite solar cells at as‐prepared and degraded states. This method is used to predict the cell performance from material selection until completion early. It also allows monitoring of the uniformity and repeatability of the cell fabrication process.